Plasma circulating cell-free mitochondrial DNA in social anxiety disorder. (February 2023) - Lindqvist, Daniel; Furmark, Tomas; Lavebratt, Catharina; Ohlsson, Lars; Månsson, Kristoffer N.T.
Abstract: Objective: To investigate plasma levels of circulating cell-free mitochondrial DNA (ccf-mtDNA) in patients with social anxiety disorder (SAD) and healthy controls (HC). Methods: In this study, 88 participants (46 patients with SAD and 42 HCs) were enrolled and both ccf-mtDNA and peripheral blood mononuclear cells (PBMC) mtDNA copy number (mtDNA-cn) were measured at up to three times per individual (9–11 weeks apart). SAD patients also received cognitive behavioral therapy (CBT) between the second and third time-point. Results: SAD patients had significantly lower ccf-mtDNA compared to HCs at all time points, but ccf-mtDNA did not change significantly after CBT, and was not associated with severity of anxiety symptoms. Plasma ccf-mtDNA did not significantly correlate with PBMC mtDNA-cn in patients. Conclusion: This is the first report of lower ccf-mtDNA in patients with an anxiety disorder. Our findings could reflect a more chronic illness course in SAD patients with prolonged periods of psychological stress leading to decreased levels of ccf-mtDNA, but future longitudinal studies are needed to confirm or refute this hypothesis. Highlights: Circulating cell-free mitochondrial DNA (ccf-mtDNA) was decreased in social anxiety disorder (SAD). The difference in ccf-mtDNA between SAD patients and controls was stable across multiple time points. Ccf-mtDNA was not affected by cognitive behavioral therapy. Ccf-mtDNA was not associated with mtDNA copy number in peripheral blood mononuclear cells.